Polish adaptation of the driving and riding avoidance scale - Błachnio, Agata; Przepiórka, Aneta; Sullman, Mark; Taylor, Joanne (De Gruyter, 2013)
Driving anxiety is a relatively undervalued topic of research, despite the fact that it can have a substantial detrimental impact on an individuals' life. The prevalence of driving anxiety in motor vehicle crash (MVC) survivors has been found to range from 18-77%. Although driving anxiety can develop without crash involvement, no information currently exists on the prevalence of driving anxiety in the general population. One barrier to gathering this information is that most of the instruments are designed to measure driving anxiety in MVC survivors. However, the Driving and Riding Avoidance Scale (DRAS; Stewart & St. Peter, 2004) is one instrument that shows promise as a more general measure of driving anxiety, although previous research has noted the need for some minor adaptations (Taylor & Sullman, 2009). Therefore, the present study investigated the psychometric properties of an adapted version of the DRAS and the level of driving anxiety amongst a sample of 210 Polish participants. Internal consistency for the overall DRAS was .91 and ranged from .77 to .85 for the subscales. Factor analysis of the DRAS resulted in two clear factors, with the first containing driving avoidance items and the second consisting solely of riding avoidance items. Therefore it appears that the DRAS can be a useful measure of driving avoidance in samples drawn from the general population as well as MVC survivors.
Keywords: driving anxiety; the Driving and Riding Avoidance Scale; self-esteem; anxiety